Bioremediation of Petroleum Hydrocarbons in Seawater: Prospects of Using Lyophilized Native Hydrocarbon-Degrading Bacteria - Rafaela Perdigão (MDPI AG, 2021)
This work aimed to develop a bioremediation product of lyophilized native bacteria to respond to marine oil spills. Three oil-degrading bacterial strains (two strains of Rhodococcus erythropolis and one Pseudomonas sp.), isolated from the NW Portuguese coast, were selected for lyophilization after biomass growth optimization (tested with alternative carbon sources). Results indicated that the bacterial strains remained viable after the lyophilization process, without losing their biodegradation potential. The biomass/petroleum ratio was optimized, and the bioremediation efficiency of the lyophilized bacterial consortium was tested in microcosms with natural seawater and petroleum. An acceleration of the natural oil degradation process was observed, with an increased abundance of oil-degraders after 24 h, an emulsion of the oil/water layer after 7 days, and an increased removal of total petroleum hydrocarbons (47%) after 15 days. This study provides an insight into the formulation and optimization of lyophilized bacterial agents for application in autochthonous oil bioremediation.